Temporal relationship between symptom cluster and quality of life in rectal cancer patients after laparoscopic anus-preserving surgery - Chaoxiang You; Guiqiong Xie; Shun Lin; Shuang Li; Mengying Jia; Xiufei Wu; Xiaoxuan Zhang; Yi Zhou; Hongyan Kou (Scientific Reports)
Abstract Although it is generally recognized that symptom clusters and quality of life are related, major ambiguity arises from the difficulty in determining their causal relationship. The present study aimed to investigate longitudinal causal relationships between symptom clusters and quality of life. 128 patients with rectal cancer from Nanchong City, Sichuan Province who underwent laparoscopic anus-preserving surgery completed 4 follow-up visits, and the survey time point are 2 weeks after surgery (T1), 1 month after surgery (T2), 3 months after surgery (T3), and 6 months after surgery (T4). We used the Anderson Gastrointestinal Cancer Symptom Assessment Scale and the Colorectal Cancer Quality of Life Measurement Scale to evaluate the patient’s symptom incidence, symptom severity, and quality of life at four time points respectively. After extracting symptom clusters by symptom, we constructed A four-wave cross-lagged model analyzed the causal relationship between symptom clusters and quality of life. Our research results show that the patients with rectal cancer treated by laparoscopic anus-preserving surgery have four symptom clusters during the 6 months after surgery, which are named sickness symptom cluster, gastrointestinal symptom cluster, psychological-sleep symptom cluster and Psycho-therapy related symptom clusters. Pearson correlation analysis showed that symptom clusters and quality of life were negatively correlated. The cross-lagged path effect coefficient shows that the impact of quality of life on symptom clusters is stronger than the impact of symptom clusters on quality of life (β = − 0.164 to − 0.713, P<0.05). The four-wave cross-lagged model showed that quality of life can significantly negatively predict the sickness symptom cluster and gastrointestinal symptom cluster, but this relationship is not bidirectional. Only T3 quality of life significantly negatively predicted the psycho-sleep symptom cluster, and the reverse path was also not observed. These findings provide evidence that decreases in quality of life levels precede increases in symptom cluster severity. There is a one-way temporal correlation between symptom clusters and quality of life. The decrease in quality of life leads to an increase in the severity of symptom clusters. The improvement in overall quality of life is expected to alleviate the distress of symptom clusters.